Synthesis and Antiproliferative Effect of 3,4,5-Trimethoxylated Chalcones on Colorectal and Prostatic Cancer Cells - Cécile Letulle; François-Xavier Toublet; Aline Pinon; Soufyane Hba; Aurélie Laurent; Vincent Sol; Catherine Fagnère; Benjamin Rioux; Florent Allais; Sophie Michallet; Laurence Lafanechère; Youness Limami; et al. (MDPI AG, 2024)
In the context of designing innovative anticancer agents, the synthesis of a series of chalcones bearing a 3,4,5-trimethoxylated A ring and a variety of B rings, including phenols and original heterocycles such as chromones, was conducted. For this end, Claisen-Schmidt condensation was performed in basic or acidic conditions between the common starting material 3,4,5-trimethoxyacetophenone and appropriate aldehydes; this allowed the recovery of fifteen chalcones in moderate-good yields. The synthesized compounds were screened for their antiproliferative activity against colorectal and prostatic cancer cells, using a colorimetric MTT assay. Among the new chromonyl series, chalcone 13 demonstrates an interesting antiproliferative effect, with IC50 values in the range of 2.6-5.1 µM at 48 h. Then, our study evidenced that indolyl chalcone 10 exhibits excellent activity towards the selected cell lines (with IC50 less than 50 nM). This compound has already been described and has been shown to be a potent anticancer agent against other cancer cell lines. Our investigations highlighted apoptosis induction, through several pro-apoptotic markers, of these two heterocyclic chalcones. Considering phenolic chalcones, compounds 2 and 8 were found to be the most active against cell proliferation, exerting their effect by inducing the depolymerization of cell microtubules. The most promising compounds in this series will be selected for application in a strategy of vectorization by either active or passive targeting.